PTFE composite material for corrugated pipe fittings and preparation method thereof
By using modified PTFE resin, polyamide resin and polyethylene resin in the bellows fitting materials, and adding toughening fillers and lubricants, the problems of insufficient strength, toughness and processing performance of existing materials are solved, and higher mechanical strength, toughness and service life are achieved.
Patent Information
- Application Number
- CN202411321077.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing bellows fitting materials have shortcomings in strength, toughness and machining performance, resulting in short service life and unstable processing.
Modified PTFE resin, polyamide resin and polyethylene resin are used as the matrix material, and specific toughening fillers, suitable lubricants and antistatic agents are added. The mechanical strength and toughness of the material are improved by the preparation method of modified PTFE resin and the preparation method of toughening fillers.
It significantly improves the mechanical strength, toughness and processing properties of corrugated pipe fitting materials, extends service life, and improves the impact resistance and stability of the materials.
Smart Images

Figure BDA0005053922330000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and in particular relates to a PTFE composite material for corrugated pipe fittings and a preparation method thereof. Background Art
[0002] Bellows is a common elastic part. It uses the elasticity of the material to achieve functions such as conversion, compensation, connection and energy storage. It is a pipeline product with wide application value. The bellows is corrugated and has good elasticity, corrosion resistance, strong pressure resistance and light weight. It is mainly used in aerospace, petrochemical, construction, water supply and drainage, power communication and other fields. It plays an important role in connection, compensation, sealing and shock absorption. Its structure is compact and adopts corrugated structure design, which makes the pipeline more flexible in bending, expansion and contraction, and is easy to install and disassemble. The commonly used materials for bellows are metals and plastics, among which metals include stainless steel, brass, bronze, etc., and plastics include polypropylene, polyethylene, nylon, polyethylene, polytetrafluoroethylene, etc. Stainless steel bellows have high bending fatigue strength and good welding performance. They are often used to connect oil storage tanks and oil pipelines. Bronze bellows have the advantages of small hysteresis and elastic aftereffect, high stability and non-magnetism. They are mainly used for high-precision measuring instruments. Plastic bellows can be made into cable casings for communication cables, underground cable pipes, ventilation pipes, water pipes, etc. In addition, the application of corrugated pipes in the aerospace field not only improves the performance of aircraft, but also reduces maintenance costs. In the petrochemical industry, corrugated pipes can withstand high temperature and high pressure environments, ensuring the safety and stability of the production process. In the construction field, corrugated pipes are used as water supply and drainage pipes, with good vibration resistance and pressure resistance, ensuring the normal use of buildings. In the power communication industry, corrugated pipes are used for cable protection and connection, which not only improves the service life of cables, but also reduces line failure rates. Corrugated pipes are also widely used in automobiles, ships, air conditioners, boilers and other industries.
[0003] For example, Chinese patent CN106867160A discloses a PTFE composite material and a preparation method thereof, wherein the raw materials for preparing the composite material include: PTFE powder, continuous fiber, filler powder, wherein the PTFE powder is a suspension polytetrafluoroethylene powder, the continuous fiber is a continuous fiber dispersed by an untwisting machine, and the filler powder is Al. The patent modifies polytetrafluoroethylene by using a certain proportion of continuous fiber and filler powder, thereby effectively improving the mechanical properties of the PTFE composite material. Chinese patent CN106867169A discloses a preparation method for a composite material for a natural gas pipeline corrugated pipe, wherein the composite material includes the following raw materials: polytetrafluoroethylene, acrylate rubber, brominated butyl rubber, fluororubber, white carbon black, dioctyl ester, rubber T-78, zinc oxide, ferrocene, zinc stearate, lead tetroxide, accelerator TBZTD, accelerator CZ. The patent improves the strength of the composite material for the corrugated pipe to a certain extent by adding inorganic auxiliary materials, and the prepared corrugated pipe can meet the strength requirements of the natural gas pipeline and has good compressibility. Chinese patent CN109535702A discloses a nylon corrugated pipe composite material and its preparation method, the composite material is mainly made of the following components: nylon 6, flame retardant, heat stabilizer, toughening agent, cold resistance agent, wherein the toughening agent is silicone powder or silicone masterbatch, and the cold resistance agent is maleic anhydride grafted EPDM rubber or maleic anhydride grafted POE or a mixture of the two. The production process of the corrugated pipe composite material prepared by the patent is simple and low in cost, which increases the application range of corrugated pipe products in the automotive industry. The present invention aims to provide a PTFE composite material for corrugated pipe fittings, which has the advantages of high strength, good toughness, stable processing performance, and long service life. Summary of the invention
[0004] In view of the deficiencies in the above-mentioned prior art, the present invention provides a PTFE composite material for corrugated pipe fittings, which uses modified PTFE, polyamide and polyethylene resins as matrix materials, and adds specific toughening fillers and suitable lubricants and antistatic agents, effectively improving the comprehensive properties of the PTFE composite material such as mechanical strength and toughness, thereby making the processing performance of the corrugated pipe fittings stable and the service life long. The present invention also provides a preparation method of the above-mentioned PTFE composite material.
[0005] The technical solution adopted by the present invention is:
[0006] A PTFE composite material for corrugated pipe fittings is prepared from the following raw materials:
[0007] Modified PTFE resin, polyamide resin, polyethylene resin, toughening filler, lubricant, antistatic agent.
[0008] A PTFE composite material for corrugated pipe fittings is prepared from the following raw materials in parts by weight:
[0009] 70-90 parts by weight of modified PTFE resin, 10-30 parts by weight of polyamide resin, 10-30 parts by weight of polyethylene resin, 5-10 parts by weight of toughening filler, 1-3 parts by weight of lubricant, and 1-3 parts by weight of antistatic agent.
[0010] Preferably, the modified PTFE resin preparation method is as follows:
[0011] Tetrafluoroethylene, perfluorobutylethylene, perfluoro-2-butene and an initiator are mixed and polymerized to obtain a polymer; γ-ureapropyltriethoxysilane, methanol and water are mixed, heated and stirred to obtain a modified liquid; the above polymer and the modified liquid are mixed, ultrasonically treated, then stirred for reaction, centrifuged and dried to obtain a modified PTFE resin.
[0012] Conventional polytetrafluoroethylene resins cannot be prepared by melt extrusion and extrusion granulation with other resins due to their high melt viscosity. Therefore, the modified PTFE resin used in the present invention is prepared by polymerization reaction of tetrafluoroethylene, perfluorobutylethylene and perfluoro-2-butene as monomers under the action of an initiator, and the processing properties of the PTFE resin are greatly improved by polymerization modification while maintaining the original physical and chemical properties. Perfluorobutylethylene and perfluoro-2-butene in a certain ratio are added to participate in copolymerization, and introduced into the molecular structure of the PTFE resin, breaking the original linear unbranched symmetrical structure, thereby reducing the melt viscosity of the PTFE resin and improving the processing properties; in addition, the present invention also finds that the introduction of perfluoro-2-butene monomers has a certain improvement in the tensile properties and impact resistance of the composite material.
[0013] On this basis, the present invention also uses a modification liquid made of γ-ureapropyltriethoxysilane, methanol and water to modify the surface of the PTFE resin, which effectively improves the compatibility between the modified PTFE resin and the polyamide resin and the polyethylene resin, ensures that the composite material has better comprehensive performance, and helps to improve processing stability.
[0014] Preferably, the modified PTFE resin preparation method is as follows:
[0015] 60-80 parts by weight of tetrafluoroethylene, 5-7 parts by weight of perfluorobutylethylene, 3-5 parts by weight of perfluoro-2-butene and 0.01-0.03 parts by weight of initiator are mixed, and polymerization reaction is carried out at 70-75°C and 1-2MPa for 3-5 hours to obtain a polymer; 1-3 parts by weight of γ-ureapropyltriethoxysilane, 30-40 parts by weight of methanol and 5-15 parts by weight of water are mixed, and stirring is carried out at 40-45°C for 0.2-0.6 hours to obtain a modified liquid; the above polymer is mixed with the modified liquid, and ultrasonic treatment is carried out at 100-300W and 20-30kHz for 0.2-0.6 hours, the solid-liquid ratio of the polymer to the modified liquid is 1kg:3-5L, and then stirring reaction is carried out at 60-70°C for 3-5 hours, centrifugation, and drying to obtain a modified PTFE resin.
[0016] Preferably, the melt flow rate of the modified PTFE resin under the test conditions of 190° C. and 2.16 kg is 6-12 g / 10 min.
[0017] Preferably, the initiator is one or a mixture of two or more of diisopropyl peroxydicarbonate, di-n-butyl peroxydicarbonate, and benzoyl peroxide.
[0018] Preferably, the preparation method of the toughening filler is as follows:
[0019] The talc powder, L-lysine diisocyanate and N,N-dimethylformamide are mixed, ultrasonically treated, and then epoxy resin is added, stirred for reaction, centrifuged and dried to obtain epoxy-modified talc powder; the epoxy-modified talc powder, N-(2-hydroxyethyl) dodecylamide and N,N-dimethylformamide are mixed, stirred for reaction, then heated and continued to stir for reaction, centrifuged and dried to obtain a toughened filler.
[0020] The toughening filler used in the present invention has talcum powder as a main component. When the PTFE composite material is impacted by external force, the talcum powder can serve as a stress concentration point to help disperse and transfer impact energy. This stress dispersion effect can reduce the expansion of cracks inside the material, making the crack expansion path tortuous and consuming more energy, thereby improving the impact resistance of the composite material.
[0021] However, directly adding talcum powder has the problem of poor dispersibility with the matrix resin and easy local agglomeration. Therefore, when preparing toughening filler, the present invention uses L-lysine diisocyanate as a bridge to realize the modification of the surface of talcum powder by epoxy resin, and participates in crosslinking and curing through epoxy ring opening, which significantly improves the dispersibility of talcum powder in the matrix resin, and further uses N-(2-hydroxyethyl) dodecylamide to react with the surface group of epoxy-modified talcum powder to introduce a long-chain flexible structure, which effectively improves the compatibility between the toughening filler and the matrix resin, so that the obtained PTFE composite material has better impact resistance and stability, and the service life is greatly improved.
[0022] Preferably, the preparation method of the toughening filler is as follows:
[0023] 7-10 parts by weight of talc, 1-3 parts by weight of L-lysine diisocyanate and 80-100 parts by weight of N,N-dimethylformamide are mixed, and ultrasonic treatment is performed at 100-300W and 20-30kHz for 0.2-0.6h, and then 1-3 parts by weight of epoxy resin are added, and the mixture is stirred and reacted at 80-90°C and nitrogen atmosphere for 5-8h, centrifuged and dried to obtain epoxy-modified talc; 1-3 parts by weight of epoxy-modified talc, 0.3-0.5 parts by weight of N-(2-hydroxyethyl) dodecylamide and 20-40 parts by weight of N,N-dimethylformamide are mixed, and the mixture is stirred and reacted at 40-50°C for 1-3h, and then the mixture is heated to 75-80°C and stirred and reacted for 2-4h, centrifuged and dried to obtain a toughened filler.
[0024] Preferably, the lubricant is one or a mixture of two or more of glyceryl stearate, pentaerythritol stearate, oxidized polyethylene wax, calcium stearate, and silicone powder.
[0025] Preferably, the antistatic agent is one or a mixture of two or more of palmitamidopropyl trimethylammonium chloride, polyoxyethylene sorbitan monostearate, and coconut fatty acid diethylamide.
[0026] In a specific implementation manner, the polyamide resin is PA66 EPR27 produced by Pingdingshan Shenma Engineering Plastics Co., Ltd., and has a melt flow rate of 10.8 g / 10 min under the test conditions of 235° C. and 2.16 kg.
[0027] In a specific implementation manner, the polyethylene resin is HDPE DGDA 6098 produced by Sinopec Qilu Petrochemical Company, and its melt flow rate under the test conditions of 190° C. and 2.16 kg is 11.5 g / 10 min.
[0028] In a specific embodiment, the epoxy resin is epoxy resin E51, with a solid content of 99%, a viscosity of 7000-10000 mPa·s (25° C.), and an epoxy equivalent of 180-190 g / eq.
[0029] The present invention also provides a method for preparing a PTFE composite material for a corrugated pipe fitting, comprising the following steps:
[0030] Weigh each raw material according to the formula, add modified PTFE resin, polyamide resin, polyethylene resin, toughening filler, lubricant, and antistatic agent into a mixer, stir and mix for 2-8 minutes to obtain a mixed material;
[0031] The mixed material is transferred into a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain the PTFE composite material for corrugated pipe fittings, wherein the extrusion temperature is 240-260° C. and the screw speed is 100-150 rpm.
[0032] Beneficial effects of the present invention:
[0033] The PTFE composite material for corrugated pipe fittings prepared by the present invention adopts modified PTFE, polyamide and polyethylene resins as matrix materials, and adds specific toughening fillers and suitable lubricants and antistatic agents, which effectively improves the comprehensive properties of the PTFE composite material such as mechanical strength and toughness, thereby making the processing performance of the corrugated pipe fittings stable and the service life long. DETAILED DESCRIPTION
[0034] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.
[0035] Example 1
[0036] A PTFE composite material for corrugated pipe fittings is prepared from the following raw materials:
[0037] 80 parts by weight of modified PTFE resin, 20 parts by weight of polyamide resin, 20 parts by weight of polyethylene resin, 7 parts by weight of toughening filler, 1.5 parts by weight of lubricant pentaerythritol stearate, and 1.5 parts by weight of antistatic agent palmitamide propyl trimethyl ammonium chloride.
[0038] The modified PTFE resin preparation method is as follows:
[0039] 70 parts by weight of tetrafluoroethylene, 6 parts by weight of perfluorobutylethylene, 4 parts by weight of perfluoro-2-butene and 0.02 parts by weight of initiator diisopropyl peroxydicarbonate were mixed, and polymerized at 72°C and 1.8MPa for 4.5 hours to obtain a polymer; 2.5 parts by weight of γ-ureapropyl triethoxysilane (CAS: 23779-32-0), 35 parts by weight of methanol and 10 parts by weight of water were mixed, and stirred at 42°C for 0.5 hours to obtain a modified liquid; the above polymer was mixed with the modified liquid, and ultrasonically treated at 200W and 25kHz for 0.5 hours, the solid-liquid ratio of the polymer to the modified liquid was 1kg:4L, and then stirred at 65°C for 4.5 hours, centrifuged, and dried to obtain a modified PTFE resin. Among them, the melt flow rate of the modified PTFE resin under the test conditions of 190°C and 2.16kg is 8.0g / 10min.
[0040] The preparation method of the toughening filler is as follows:
[0041] 8.5 parts by weight of talc (water content ≤ 0.05%, fineness 3000 mesh), 1.5 parts by weight of L-lysine diisocyanate and 90 parts by weight of N, N-dimethylformamide are mixed, ultrasonically treated at 200 W and 25 kHz for 0.5 h, and then 2 parts by weight of epoxy resin are added, stirred and reacted at 86° C. in a nitrogen atmosphere for 6.5 h, centrifuged and dried to obtain epoxy-modified talc; 2 parts by weight of epoxy-modified talc, 0.4 parts by weight of N-(2-hydroxyethyl) dodecylamide (CAS: 142-78-9) and 30 parts by weight of N, N-dimethylformamide are mixed, stirred and reacted at 45° C. for 2 h, then the temperature is raised to 78° C. and the stirring reaction is continued for 3 h, centrifuged and dried to obtain a toughened filler.
[0042] The method for preparing the PTFE composite material for corrugated pipe fittings comprises the following steps:
[0043] Weigh each raw material according to the formula, add modified PTFE resin, polyamide resin, polyethylene resin, toughening filler, lubricant, and antistatic agent into a mixer, stir and mix for 5 minutes to obtain a mixed material;
[0044] The mixed material is transferred into a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain the PTFE composite material for corrugated pipe fittings. The extrusion temperature is: 240°C for zone 1, 250°C for zone 2, 255°C for zone 3, 255°C for zone 4, 260°C for die head, and 120rpm for screw speed.
[0045] Example 2
[0046] A PTFE composite material for corrugated pipe fittings is prepared from the following raw materials:
[0047] 70 parts by weight of modified PTFE resin, 10 parts by weight of polyamide resin, 10 parts by weight of polyethylene resin, 5 parts by weight of toughening filler, 1 part by weight of lubricant, and 1 part by weight of antistatic agent.
[0048] The preparation method of the modified PTFE resin is the same as that in Example 1.
[0049] The preparation method of the toughening filler is the same as that of Example 1.
[0050] The preparation method of the PTFE composite material for corrugated pipe fittings is the same as that in Example 1.
[0051] Example 3
[0052] A PTFE composite material for corrugated pipe fittings is prepared from the following raw materials:
[0053] 90 parts by weight of modified PTFE resin, 30 parts by weight of polyamide resin, 30 parts by weight of polyethylene resin, 10 parts by weight of toughening filler, 3 parts by weight of lubricant, and 3 parts by weight of antistatic agent.
[0054] The preparation method of the modified PTFE resin is the same as that in Example 1.
[0055] The preparation method of the toughening filler is the same as that of Example 1.
[0056] The preparation method of the PTFE composite material for corrugated pipe fittings is the same as that in Example 1.
[0057] Example 4
[0058] A PTFE composite material for corrugated pipe fittings is prepared from the following raw materials:
[0059] 80 parts by weight of modified PTFE resin, 20 parts by weight of polyamide resin, 20 parts by weight of polyethylene resin, 7 parts by weight of toughening filler, 1.5 parts by weight of lubricant pentaerythritol stearate, and 1.5 parts by weight of antistatic agent palmitamide propyl trimethyl ammonium chloride.
[0060] The modified PTFE resin preparation method is as follows:
[0061] 70 parts by weight of tetrafluoroethylene, 6 parts by weight of perfluorobutylethylene, 4 parts by weight of perfluoro-2-butene and 0.02 parts by weight of diisopropyl peroxydicarbonate as an initiator were mixed, and polymerized at 72° C. and 1.8 MPa for 4.5 hours to obtain a modified PTFE resin. The melt flow rate of the modified PTFE resin under the test conditions of 190° C. and 2.16 kg was 8.0 g / 10 min.
[0062] The preparation method of the toughening filler is as follows:
[0063] 8.5 parts by weight of talc (water content ≤ 0.05%, fineness 3000 mesh), 1.5 parts by weight of L-lysine diisocyanate and 90 parts by weight of N, N-dimethylformamide are mixed, ultrasonically treated at 200 W and 25 kHz for 0.5 h, and then 2 parts by weight of epoxy resin are added, stirred and reacted at 86° C. in a nitrogen atmosphere for 6.5 h, centrifuged and dried to obtain epoxy-modified talc; 2 parts by weight of epoxy-modified talc, 0.4 parts by weight of N-(2-hydroxyethyl) dodecylamide (CAS: 142-78-9) and 30 parts by weight of N, N-dimethylformamide are mixed, stirred and reacted at 45° C. for 2 h, then the temperature is raised to 78° C. and the stirring reaction is continued for 3 h, centrifuged and dried to obtain a toughened filler.
[0064] The method for preparing the PTFE composite material for corrugated pipe fittings comprises the following steps:
[0065] Weigh each raw material according to the formula, add modified PTFE resin, polyamide resin, polyethylene resin, toughening filler, lubricant, and antistatic agent into a mixer, stir and mix for 5 minutes to obtain a mixed material;
[0066] The mixed material is transferred into a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain the PTFE composite material for corrugated pipe fittings. The extrusion temperature is: 240°C for zone 1, 250°C for zone 2, 255°C for zone 3, 255°C for zone 4, 260°C for die head, and 120rpm for screw speed.
[0067] Example 5
[0068] A PTFE composite material for corrugated pipe fittings is prepared from the following raw materials:
[0069] 80 parts by weight of modified PTFE resin, 20 parts by weight of polyamide resin, 20 parts by weight of polyethylene resin, 7 parts by weight of toughening filler, 1.5 parts by weight of lubricant pentaerythritol stearate, and 1.5 parts by weight of antistatic agent palmitamide propyl trimethyl ammonium chloride.
[0070] The modified PTFE resin preparation method is as follows:
[0071] 70 parts by weight of tetrafluoroethylene, 10 parts by weight of perfluorobutylethylene and 0.02 parts by weight of initiator diisopropyl peroxydicarbonate are mixed, and polymerization reaction is carried out at 72° C. and 1.8 MPa for 4.5 hours to obtain a polymer; 2.5 parts by weight of γ-ureapropyltriethoxysilane (CAS: 23779-32-0), 35 parts by weight of methanol and 10 parts by weight of water are mixed, and stirred at 42° C. for 0.5 hours to obtain a modified liquid; the above polymer is mixed with the modified liquid, and ultrasonic treatment is carried out at 200 W and 25 kHz for 0.5 hours, the solid-liquid ratio of the polymer to the modified liquid is 1 kg:4L, and then stirred and reacted at 65° C. for 4.5 hours, centrifuged, and dried to obtain a modified PTFE resin.
[0072] The preparation method of the toughening filler is as follows:
[0073] 8.5 parts by weight of talc (water content ≤ 0.05%, fineness 3000 mesh), 1.5 parts by weight of L-lysine diisocyanate and 90 parts by weight of N, N-dimethylformamide are mixed, ultrasonically treated at 200 W and 25 kHz for 0.5 h, and then 2 parts by weight of epoxy resin are added, stirred and reacted at 86° C. in a nitrogen atmosphere for 6.5 h, centrifuged and dried to obtain epoxy-modified talc; 2 parts by weight of epoxy-modified talc, 0.4 parts by weight of N-(2-hydroxyethyl) dodecylamide (CAS: 142-78-9) and 30 parts by weight of N, N-dimethylformamide are mixed, stirred and reacted at 45° C. for 2 h, then the temperature is raised to 78° C. and the stirring reaction is continued for 3 h, centrifuged and dried to obtain a toughened filler.
[0074] The method for preparing the PTFE composite material for corrugated pipe fittings comprises the following steps:
[0075] Weigh each raw material according to the formula, add modified PTFE resin, polyamide resin, polyethylene resin, toughening filler, lubricant, and antistatic agent into a mixer, stir and mix for 5 minutes to obtain a mixed material;
[0076] The mixed material is transferred into a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain the PTFE composite material for corrugated pipe fittings. The extrusion temperature is: 240°C for zone 1, 250°C for zone 2, 255°C for zone 3, 255°C for zone 4, 260°C for die head, and 120rpm for screw speed.
[0077] Example 6
[0078] A PTFE composite material for corrugated pipe fittings is prepared from the following raw materials:
[0079] 80 parts by weight of modified PTFE resin, 20 parts by weight of polyamide resin, 20 parts by weight of polyethylene resin, 7 parts by weight of toughening filler, 1.5 parts by weight of lubricant pentaerythritol stearate, and 1.5 parts by weight of antistatic agent palmitamide propyl trimethyl ammonium chloride.
[0080] The modified PTFE resin preparation method is as follows:
[0081] 70 parts by weight of tetrafluoroethylene, 6 parts by weight of perfluorobutylethylene, 4 parts by weight of perfluoro-2-butene and 0.02 parts by weight of initiator diisopropyl peroxydicarbonate were mixed, and polymerized at 72°C and 1.8MPa for 4.5 hours to obtain a polymer; 2.5 parts by weight of γ-ureapropyl triethoxysilane (CAS: 23779-32-0), 35 parts by weight of methanol and 10 parts by weight of water were mixed, and stirred at 42°C for 0.5 hours to obtain a modified liquid; the above polymer was mixed with the modified liquid, and ultrasonically treated at 200W and 25kHz for 0.5 hours, the solid-liquid ratio of the polymer to the modified liquid was 1kg:4L, and then stirred at 65°C for 4.5 hours, centrifuged, and dried to obtain a modified PTFE resin. Among them, the melt flow rate of the modified PTFE resin under the test conditions of 190°C and 2.16kg is 8.0g / 10min.
[0082] The preparation method of the toughening filler is as follows:
[0083] 8.5 parts by weight of talc (water content ≤ 0.05%, fineness 3000 mesh), 1.5 parts by weight of L-lysine diisocyanate and 90 parts by weight of N,N-dimethylformamide were mixed, ultrasonically treated at 200 W and 25 kHz for 0.5 h, and then 2 parts by weight of epoxy resin were added. The mixture was stirred and reacted at 86° C. in a nitrogen atmosphere for 6.5 h, centrifuged, and dried to obtain a toughened filler.
[0084] The method for preparing the PTFE composite material for corrugated pipe fittings comprises the following steps:
[0085] Weigh each raw material according to the formula, add modified PTFE resin, polyamide resin, polyethylene resin, toughening filler, lubricant, and antistatic agent into a mixer, stir and mix for 5 minutes to obtain a mixed material;
[0086] The mixed material is transferred into a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain the PTFE composite material for corrugated pipe fittings. The extrusion temperature is: 240°C for zone 1, 250°C for zone 2, 255°C for zone 3, 255°C for zone 4, 260°C for die head, and 120rpm for screw speed.
[0087] Example 7
[0088] A PTFE composite material for corrugated pipe fittings is prepared from the following raw materials:
[0089] 80 parts by weight of modified PTFE resin, 20 parts by weight of polyamide resin, 20 parts by weight of polyethylene resin, 7 parts by weight of toughening filler, 1.5 parts by weight of lubricant pentaerythritol stearate, and 1.5 parts by weight of antistatic agent palmitamide propyl trimethyl ammonium chloride.
[0090] The modified PTFE resin preparation method is as follows:
[0091] 70 parts by weight of tetrafluoroethylene, 6 parts by weight of perfluorobutylethylene, 4 parts by weight of perfluoro-2-butene and 0.02 parts by weight of initiator diisopropyl peroxydicarbonate were mixed, and polymerized at 72°C and 1.8MPa for 4.5 hours to obtain a polymer; 2.5 parts by weight of γ-ureapropyl triethoxysilane (CAS: 23779-32-0), 35 parts by weight of methanol and 10 parts by weight of water were mixed, and stirred at 42°C for 0.5 hours to obtain a modified liquid; the above polymer was mixed with the modified liquid, and ultrasonically treated at 200W and 25kHz for 0.5 hours, the solid-liquid ratio of the polymer to the modified liquid was 1kg:4L, and then stirred at 65°C for 4.5 hours, centrifuged, and dried to obtain a modified PTFE resin. Among them, the melt flow rate of the modified PTFE resin under the test conditions of 190°C and 2.16kg is 8.0g / 10min.
[0092] The preparation method of the toughening filler is as follows:
[0093] Mix 2 parts by weight of talc (water content ≤ 0.05%, fineness 3000 mesh), 0.4 parts by weight of N-(2-hydroxyethyl) dodecylamide (CAS: 142-78-9) and 30 parts by weight of N,N-dimethylformamide, stir and react at 45°C for 2 hours, then heat to 78°C and continue stirring and reacting for 3 hours, centrifuge and dry to obtain a toughened filler.
[0094] The method for preparing the PTFE composite material for corrugated pipe fittings comprises the following steps:
[0095] Weigh each raw material according to the formula, add modified PTFE resin, polyamide resin, polyethylene resin, toughening filler, lubricant, and antistatic agent into a mixer, stir and mix for 5 minutes to obtain a mixed material;
[0096] The mixed material is transferred into a twin-screw extruder for melt extrusion, cooling, and pelletizing to obtain the PTFE composite material for corrugated pipe fittings. The extrusion temperature is: 240°C for zone 1, 250°C for zone 2, 255°C for zone 3, 255°C for zone 4, 260°C for die head, and 120rpm for screw speed.
[0097] Test Example 1
[0098] The tensile properties of the PTFE composite material obtained in the above embodiment were measured with reference to the method in GB / T 1040.2-2022, the tensile rate was 50 mm / min, and the dumbbell-shaped sample size was 80×10×4 mm. The impact resistance of the PTFE composite material obtained in the above embodiment was measured with reference to the method in GB / T 1843-2008, the sample notch type was type A, and the size was 80×10×4 mm. Five parallel groups were measured, and the average value was taken. The results are shown in Table 1.
[0099] Table 1 Tensile strength and impact strength of PTFE composite materials
[0100]
[0101] Test Example 2
[0102] After the PTFE composite material obtained in the above example was placed in a constant temperature and humidity chamber (temperature 90°C, relative humidity 95%) for 5 weeks, the impact resistance of the PTFE composite material was measured again with reference to the method in GB / T 1843-2008, and the impact strength retention rate was calculated. Impact strength retention rate = (initial notched impact strength - notched impact strength after 5 weeks) / initial notched impact strength × 100%, 5 groups were paralleled, and the average value was taken. The results are shown in Table 2.
[0103] Table 2 Impact strength retention of PTFE composite materials
[0104] Impact strength retention rate / % Example 1 97.2 Example 4 93.0 Example 5 95.1 Example 6 94.6 Example 7 93.8
[0105] As can be seen from the test results, the PTFE composite material prepared by the present invention effectively improves the tensile properties, impact resistance and stability of the composite material by adopting modified special modified PTFE resin and toughening filler. This is because, compared with embodiment 4-5, the modified PTFE resin used in embodiment 1-3 of the present invention is modified by polymerization to make it while maintaining the original physical and chemical properties, greatly improve the processing properties of PTFE resin, by adding a certain ratio of perfluorobutyl ethylene, perfluoro-2-butene to participate in copolymerization, introduce it into the PTFE resin molecular structure, break the original linear unbranched symmetrical structure, thereby reducing the melt viscosity of PTFE resin, improve processing properties, and the introduction of perfluoro-2-butene monomer also has a certain improvement for the tensile properties and impact resistance of composite materials. On this basis, the modified liquid made of γ-urea propyl triethoxy silane, methanol and water is also used to carry out surface modification of PTFE resin, effectively improve the compatibility between modified PTFE resin and polyamide resin and polyethylene resin, ensure that composite material has better comprehensive performance, and help to improve processing stability. Further, compared to Examples 6-7, the toughening filler prepared in Examples 1-3 of the present invention uses L-lysine diisocyanate as a bridge to realize the modification of the surface of talcum powder by epoxy resin, participates in cross-linking and curing through epoxy ring opening, significantly improves the dispersibility of talcum powder in the matrix resin, and further utilizes N-(2-hydroxyethyl) dodecylamide and the surface group of epoxy-modified talcum powder to undergo grafting reaction to introduce a long-chain flexible structure, effectively improving the compatibility between the toughening filler and the matrix resin, so that the obtained PTFE composite material has better impact resistance and stability, and the service life is greatly improved. When the PTFE composite material is impacted by external force, the toughening filler acts as a stress concentration point to help disperse and transmit impact energy. This stress dispersion can reduce the crack propagation inside the material, making the crack propagation path tortuous, consuming more energy, thereby improving the impact resistance of the composite material.
[0106] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A PTFE composite material for corrugated pipe fittings, characterized in that: The invention is prepared from the following raw materials: 70-90 parts by weight of modified PTFE resin, 10-30 parts by weight of polyamide resin, 10-30 parts by weight of polyethylene resin, 5-10 parts by weight of toughening filler, 1-3 parts by weight of lubricant, and 1-3 parts by weight of antistatic agent; The modified PTFE resin preparation method is as follows: Tetrafluoroethylene, perfluorobutylethylene, perfluoro-2-butene and an initiator are mixed and polymerized to obtain a polymer; γ-ureapropyltriethoxysilane, methanol and water are mixed and heated and stirred to obtain a modified liquid; the polymer and the modified liquid are mixed and ultrasonically treated, and then stirred and reacted, centrifuged and dried to obtain a modified PTFE resin; The preparation method of the toughening filler is as follows: The talc powder, L-lysine diisocyanate and N,N-dimethylformamide are mixed, ultrasonically treated, and then epoxy resin is added, stirred for reaction, centrifuged and dried to obtain epoxy-modified talc powder; the epoxy-modified talc powder, N-(2-hydroxyethyl) dodecylamide and N,N-dimethylformamide are mixed, stirred for reaction, then heated and continued to stir for reaction, centrifuged and dried to obtain a toughened filler.
2. The PTFE composite material for corrugated pipe fittings according to claim 1, characterized in that: The initiator is one or a mixture of two or more of diisopropyl peroxydicarbonate, di-n-butyl peroxydicarbonate and benzoyl peroxide.
3. The PTFE composite material for corrugated pipe fittings according to claim 1, characterized in that: The melt flow rate of the modified PTFE resin under the test conditions of 190° C. and 2.16 kg is 6-12 g / 10 min.
4. The PTFE composite material for corrugated pipe fittings according to claim 1, characterized in that: The lubricant is one or a mixture of two or more of glyceryl stearate, pentaerythritol stearate, oxidized polyethylene wax, calcium stearate and silicone powder.
5. The PTFE composite material for corrugated pipe fittings according to claim 1, characterized in that: The antistatic agent is one or a mixture of two or more of palmitamidopropyl trimethylammonium chloride, polyoxyethylene sorbitan monostearate, and coconut fatty acid diethylamide.
6. The method for preparing a PTFE composite material for a corrugated pipe according to any one of claims 1 to 5, characterized in that: The following steps are involved: Weigh the raw materials according to the formula, add the modified PTFE resin, polyamide resin, polyethylene resin, toughening filler, lubricant, and antistatic agent into a mixer, stir and mix to obtain a mixed material; The mixed material is transferred into a twin-screw extruder for melt extrusion, cooled, and pelletized to obtain the PTFE composite material for corrugated pipe fittings.
Citation Information
Patent Citations
PTFE composite material, and preparation method thereof
CN106867160A
Preparation method for composite material of corrugated pipe of natural gas pipeline
CN106867169A
Nylon corrugated-pipe composite material and preparation method thereof
CN109535702A
High ring stiffness bellows, and preparation method thereof
CN107474368A
High-resilience creep-resistant modified polytetrafluoroethylene sealing material and preparation method thereof
CN117050447A